Implementation and evaluation of patient navigation in Chicago: Insights on addressing the social determinants of health and integrating HIV prevention and care services. (February 2022) - Greene, George J.; Reidy, Emma; Felt, Dylan; Marro, Rachel; Johnson, Amy K.; Phillips, Gregory; Green, Evelyn; Stonehouse, Patrick
Highlights: Patient navigation for HIV prevention and care services is feasible and warranted. Screening for social determinants of health is a critical navigation activity. Effective navigation implementation and evaluation requires ongoing stakeholder input. Abstract: Patient navigation is a primary element in linkage to HIV pre-exposure prophylaxis (PrEP) care and linkage to or re-engagement in HIV care, depending on the HIV status of the individual. However, there is a dearth of literature describing navigation services in these areas. In the context of Chicago Project PrIDE, this project conducted process and implementation evaluations with eight agencies leading demonstration projects to address these gaps. The evaluation team conducted semi-structured, individual interviews with agency staff (N = 20) assessing navigation implementation and fit, as well as project successes and challenges. Additionally, agency staff collected patient surveys (N = 300) assessing services provided, service quality, and satisfaction. The interview transcripts were coded and analyzed thematically and descriptive analyses were performed on the survey data. Analyses indicated that screening for social determinants of health, providing healthcare engagement guidance, and providing service referrals were frequently cited navigation activities. Most staff members indicated that navigation fits well within their agencies, and that limited staff and clinic capacity were often barriers to navigation. Patient navigation to support engagement in HIV prevention and care services is critical due to the extensive support provided by navigators to address social determinants of health impacting HIV disparity populations.